How much do the crimes committed by released inmates cost?Michael Ostermann and Joel M. Caplan - Ostermann, Michael (Crime & delinquency, 2016)
The goal of this study is to explore the monetary costs of crimes committed by former inmates as they attempt to transition back into their communities. We use data gathered from New Jersey prison releases from 2005 to 2007 (n = 31,831) for our explorations. In addition to describing local-, county-, and state-level costs of crimes, we construct a series of regression models to predict costs using several predictors of recidivism. Results indicate that age, minority status, area-level deprivation, and whether the inmate was released to parole supervision were statistically significant predictors of costs in expected directions. However, strongly established predictors of recidivism such as criminal history and policy-relevant predictors such as time served are not significant predictors of postrelease costs of crimes. Our discussion presents a simple cost-benefit analysis according to two distinct policy approaches: (a) targeting evidence-based correctional principles toward high-risk former inmates and (b) incapacitating high-risk former inmates.